Desain Pembelajaran PAK Dewasa dengan Menggunakan Technological Centered Design di Bajem GEKISIA Kelapa - Mangero, Kristina; Kamagi, Kevin Samuel (Institut Agama Kristen Negeri Manado, 2024)
Church as a place to educate all age groups and form good attitudes and behavior holistically. In learning the congregation, of course, each age group is different because the understanding and spiritual formation of each age group is different. Learning for the adult age group in the church is still lacking. Some of the facts found in the church are simply providing discussions that do not grow and change attitudes and behavior of adults holistically. This happens because there is still a lack of materials in adult learning that are prepared, but also due to the busyness of adult church members so they do not have time to attend coaching classes. The method used is a qualitative research method with a literature review and literature study approach. The results of the research show that learning design using Technological Centered Design can help the church in conducting learning and coaching for adults especially in the digital era and is useful for spiritual growth, as well as the use of technology that continues to develop. So the aim of this research is to provide an effective learning design to adult at Bajem Gekisia Kelapa by using Technological Centered Design.